Towards Sustainable Economy: The Role of E-Procurement Implementation in the Delivery of Public Projects in Nigeria - Yahaya, M. L.; Babalola, A. J.; Abubakar, M. J.; Sani, M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Contracting firms spend significant resources in an attempt to participate in public project contracts in Nigeria. As such, their working capital and liquidity ratio have always been condensed. The aim of the study was to explore factors influencing the successful implementation of E-procurement for sustainable economy. To attain this goal, the quantitative approach design method was adopted. Forty-five (45) questionnaires were administered to the respondents using random sampling techniques in Lagos, South West Nigeria. Data were collected from the respondent and analyzed using a descriptive statistic in the form of mean item score (MIS), resulting in the various statistical outputs that were used to justify the research questions. The result from the analyses has shown factors such as lack of management support, I.T infrastructure, expertise and business benefit were among the first three that affect e-procurement implementation in the study area The study concludes that integrating technology approaches into the procurement policies relating to public procurement will enhance sustainable procurement and economy through legislative and government support in the area. The study therefore recommends that Construction industry professionals should be computer specialist on how the concern security of submitted tender bid and usually virus attack can be addressed. Lack of upper management support the major hindering should be considered in other to make proper implementation of e-procurement, most importantly, incorporation of educational programs for professionals (workshops, seminars, and conferences).